2007
DOI: 10.1007/s11010-007-9592-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sirt1 by resveratrol and nicotinamide alters proliferation and differentiation of pig preadipocytes

Abstract: Sirt1, a NAD + -dependent histone deacetylase, may regulate senescence, metabolism, and apoptosis. In this study, primary pig preadipocytes were cultured in DMEM/F12 medium containing 10% fetal bovine serum (FBS) with or without reagents affecting Sirt1 activity. The adipocyte differentiation process was visualized by light microscopy after Oil red O staining. Proliferation and differentiation of preadipocytes was measured using methylthiazolyldiphenyl-tetrazolium bromide (MTT) and Oil red O extraction. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 56 publications
16
101
3
1
Order By: Relevance
“…Adipogenesis is known as a hyperplastic transformation from undifferentiated pre-adipocytes to mature adipocytes and, lipogenesis, the convert and accumulation of lipid droplets in adipocyte from free fatty acids. Regarding the anti-adipogenic effects, several studies have demonstrated that resveratrol inhibited adipogenesis at concentrations of 20 to 100 μM and in the treatment period length (24 hr to 8 days) [36][37][38][39]. Our results show that resveratrol attenuated adipogenesis and lipogenesis at concentrations of 1 to 10 μM which is much less than the above published studies.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Adipogenesis is known as a hyperplastic transformation from undifferentiated pre-adipocytes to mature adipocytes and, lipogenesis, the convert and accumulation of lipid droplets in adipocyte from free fatty acids. Regarding the anti-adipogenic effects, several studies have demonstrated that resveratrol inhibited adipogenesis at concentrations of 20 to 100 μM and in the treatment period length (24 hr to 8 days) [36][37][38][39]. Our results show that resveratrol attenuated adipogenesis and lipogenesis at concentrations of 1 to 10 μM which is much less than the above published studies.…”
Section: Discussioncontrasting
confidence: 69%
“…Our study revealed distinct and much more dynamic actions of resveratrol on both high-fat diet obese mice and 3T3-L1 cells conferred by a wide range of concentrations, as compared to previous studies [35][36][37][38][39][40][41]. At low concentrations (below 10 μM), resveratrol appears to inhibit adipogenic differentiation and lipolysis.…”
Section: Discussionsupporting
confidence: 58%
“…Porcine preadipocytes were obtained as previously described (36,37). Cells were seeded in culture plates at a density of 5 × 10 4 cells/cm 2 and cultured at 37 o C in a humidified atmosphere containing 5% CO2.…”
Section: Porcine Primary Preadipocytes In Vitro Culturementioning
confidence: 99%
“…The cellular lipid contents were determined with Oil red O (Sigma, USA) and the TG contents were determined with Oil red O extraction by the method of Liang Bai et al (36). Cellular morphology was examined and photographed with a light microscope.…”
Section: Oil Red O Staining and Extractionmentioning
confidence: 99%
“…A number of research studies have suggested that the SIRT1 and SIRT2 genes enhance proliferation of preadipocytes and inhibit preadipocyte apoptosis through their acetylation/deacetylation functions (Bai et al, 2007;Wang and Tong, 2009). Similarly, recent studies have suggested that SIRT5 has a similar function in humans (Nakagawa, 2009), but its mechanism of action remains unclear.…”
Section: Introductionmentioning
confidence: 99%